Design, manufacturing and tests of the LIPAc high energy beam transport line. (24th November 2020) - Brañas, B.; Castellanos, J.; Nomen, O.; Oliver, C.; Aragón, F.; Arranz, F.; Chamorro, M.; Duglue, D.; Ferreira, J.A.; García, R.; García, J.M.; Gex, D.; et al.
Abstract: The International Fusion Materials Irradiation Facility (IFMIF) is a projected accelerator-based, D-Li neutron source for fusion reactor materials qualification. LIPAc (Linear IFMIF Prototype Accelerator) is an accelerator aiming to generate a 125 mA, 9 MeV continuous wave deuteron beam, which is currently being commissioned in Rokkasho (Japan) with the objective of validating the IFMIF accelerator design. In LIPAc, a 10 m long High Energy Beam Transport line (HEBT) will connect the exit of the superconducting linac to the beam dump (BD). The HEBT line must accommodate the diagnostics for beam characterization and open the beam at the end to allow its stopping at the BD. The line contains several magnets to control the beam shape and its trajectory, maintaining beam losses below 1 W m −1 along the beamline to limit activation of surrounding elements and allow hands-on maintenance. In this work, the LIPAc HEBT line project is described since its origins. A summary of the beam dynamics calculations and other studies (vacuum, radioprotection, assembly, alignment) that led to the conceptual design of the line is done. After that, the detailed design of the line is presented, justifying the main design decisions taken and finally, the manufacturing and procurement process and the acceptance tests performed are summarized.